Agama Buddha dan Peranan Kebudayaan Tionghoa Pada Masyarakat di Cianjur - Yuri Kuswoyo; Rubiyati Rubiyati; Rapiadi Rapiadi (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2021)
Various cultures developed in Indonesia from Sabang to Merauke. Likewise, Chinese culture in Indonesia has its own characteristics. Chinese culture in Indonesia has blended with native Indonesian culture. The culture of the Chinese community is very familiar to the Indonesian people, both from the type of food (Chinese Food), art, dance, even Barongsai. Every Cap Go Meh celebration there is always a Barongsai dance in various cities in Indonesia as well as in Cianjur City. This Barongsai dance is part of Chinese culture. The Cap Go Meh celebration is something to look forward to for both the Buddhist community and local residents who are able to unite diversity and are able to unite human beings in the archipelago (Indonesia), especially in Cianjur with religious, ethnic and cultural backgrounds that have spiritual value that is not apart from the influence of Buddhist teachings. The purpose of writing articles on Buddhism and the Role of Chinese Culture in the community in Cianjur is to be able to provide understanding and understanding of local values ​​that exist in Buddhist communities that have been integrated into the tradition so that Buddhists in each region have their own characteristics. This research is a qualitative research that is library research in which the research uses literature studies and books and also the results of field surveys.